Emerging Therapeutic Strategies for Pulmonary Fibrosis Bisas Muhammad¹, Mahnoor Malik Sohail², Syeda Tahira Zaidi³, Asia Firdous⁴, Ahmad - Bisas Muhammad, Mahnoor Malik Sohail, Syeda Tahira Zaidi, Asia Firdous, Ahmad Basirat, Sabeen Arjumand, Tehseen Mustafa (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
diopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease with limited lifeexpectancy despite current therapies. Novel approaches including biomolecule-based agents targeting fibrogenic pathways h